Radiation shielding of the sterilization installation based on gamma-radiating europium isitopes - Razsukovanyj, B.N.; Mazilov, A.A.; Mazilov, A.V. (Вопросы атомной науки и техники, 2004)
The method of calculation of a radiation protection from a source of a gamma radiation including isotopes of europium-152 and europium-154 by activity 1.5 MCi everyone is presented. As a material of protection the iron, concrete and homogeneous mixture of iron ore and concrete was used. The way of computation of radiation parameters necessary for performance of calculation of protection from nontraditional materials is shown.